THE SOCIO-HISTORICAL GENESIS OF THE EDUCATIONAL PHILOSOPHY FORMULATED IN TURKESTAN, AND ITS IMPLICATIONS - Muzaffarovna, Namazova Yulduz (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the contribution of Jadids to the effective development of education in Turkestan in the late nineteenth and early twentieth centuries, as well as the genesis development of science.